REPOSISI CITRA MELALUI LOGO Studi Kasus Perubahan Logo PT Pos Indonesia - Martadi, Martadi (Nirmana, 2002)
Logograph is a method of representing some ideal values%2C involving some aspects such as: visions and missions%2C working scopes%2C and identifying cultures of business companies%2C which playing roles in representing the facial features of any institutions or any business companies. As a symbolic language%2C it is common that a logograph is typified in a symbol%2C which is reflecting certain images that are deliberately built by concerned institutions or business companies. When a company is wishing to build a new image%2C it is necessarily to reposition the prevailed image that has been shaped in the community. Changing the appearance of the logotype of the company can make the reposition of the images. As a symbolic language%2C logos can be made up as a meant to disseminate any certain ideologies. When there have to be undertaken to uniform the applications of any certain ideological symbols upon any institutional or organisational logotypes%2C so that it can be achieving some ideological hegemony through the use of logos. And when those ideologies cannot be imaged adequately good enough%2C and their power structures cannot provide sufficient hegemonic supports%2C then those hegemonic representational symbols are attempted to be eliminated to build new images. Abstract in Bahasa Indonesia : Logo merupakan representasi dari nilai-nilai ideal%2C yang meliputi aspek: visi dan misi%2C ruang lingkup kerja%2C serta budaya perusahaan%2C dan berperan sebagai wajah suatu lembaga atau perusahaan. Sebagai bahasa penanda%2C logo biasanya ditampilkan berupa sesuatu yang mencerminkan citra tertentu yang sengaja dibangun oleh suatu lembaga atau perusahaan. Apabila suatu perusahaan ingin membangun citra yang baru%2C maka perlu upaya memposisikan ulang citra yang telah terbentuk di masyarakat. Reposisi citra dapat dilakukan dengan merubah tampilan logo perusahaan. Sebagai bahasa penanda%2C logo dapat dijadikan alat untuk menyebarluaskan suatu ideologi tertentu. Ketika dilakukan penyeragaman penggunaan tanda-tanda dari ideologi tertentu pada semua logo lembaga atau perusahaan%2C maka terjadilah hegemoni ideologi melalui logo. Manakala ideologi tersebut dicitrakan kurang baik dan struktur kekuasaan tidak kuat lagi menyokong hegemoni%2C maka tanda-tanda yang mewakili hegemoni tersebut berupaya dihilangkan untuk membangun citra baru. Reposition%2C images%2C logotype.